Strategi Peningkatan Produktivitas Kerja dengan Kompetensi dan Kompensasi Melalui Motivasi Intrinsik sebagai Variabel Intervenig pada Pegawai Bumdes Panggung Lestari, Panggungharjo, Sewon, Bantul - Zakaria, Yuni Arifin; Herawati, Jajuk (Jurnal Bingkai Ekonomi (JBE), 2021)
The research aims to determine the effect of competence, compensation, on work productivity with intrinsic motivation as an intervening variable at BUMDes Panggung Lestari, Bantul, Yogyakarta. By knowing the magnitude of the influence of the variables studied, it is hoped that it can provide good recommendations to provide strategies for increasing work productivity. employees against the organization. The method in this research is using the census method. This research is a quantitative study, the sample in this study is 51 employees. The data collection technique is done by using a questionnaire. The results of this study, namely, there is a positive and significant effect of competence on intrinsic motivation, compensation has a positive and significant effect on intrinsic motivation, competence has a positive and significant effect on work productivity, compensation has no significant effect on work productivity, intrinsic motivation has a positive and significant effect on productivity. work. The result of the sobel test shows that competency has a positive and significant effect on work productivity through intrinsic motivation as an intervening variable and compensation has a positive and significant effect on work productivity through intrinsic motivation as an intervening variable.